Effectiveness, Challenges, and Implications of Internal Quality Assurance System Implementation Before and After Covid-19 Pandemic - Tasrim, Isnada Waris (ISTAWA, 2023)
This study aims to evaluate the implementation of internal quality assurance system (IQAS) in schools before and after the COVID-19 pandemic that highlight its effectiveness, challenges and implications, using a qualitative approach with a case study design. The data was obtained through FGD, interviews, observations, and document studies and analyzed using qualitative-interactive analysis. The source of data was the IQAS team in the 8 schools studied. The findings show the implementation of internal quality assurance system (IQAS) before the COVID-19 pandemic ran quite effectively, although not all school members had the same understanding of the IQAS. However, after the COVID-19 pandemic, schools experienced many obstacles in adapting all school programs, both academic and non-academic, to emergency conditions. Because schools are required to switch to new patterns and learning processes very quickly, the implementation of IQAS cannot take place normally. The very significant change due to the COVID-19 Pandemic certainly raises many challenges faced by all schools to ensure that the learning process can continue even in very emergency conditions. One of the effective efforts made by schools is to strengthen cooperation through involving the community and parents to jointly participate actively in the implementation of learning during the COVID-19 period so that these challenges can be overcome in stages. The implication of implementing IQAS for the progress of schools is that parents and the community have more trust in school efforts in providing the best educational services for students and schools can easily solve their problems by implementing IQAS effectively.